2012
DOI: 10.5007/1980-0037.2012v14n1p83
|View full text |Cite
|
Sign up to set email alerts
|

Análise eletromiográfica dos músculos da coxa no exercício agachamento afundo até a exaustão. DOI: 10.5007/1980-0037.2012v14n1p83

Abstract: Resumo -O agachamento afundo possui um posicionamento dos membros inferiores diferencial em relação ao agachamento padrão, necessitando de maiores esclarecimentos acerca das participações dos músculos envolvidos. O objetivo foi analisar a atividade eletromiográfica dos músculos vastus lateralis (VL), vastus medialis (VM), bíceps femoris (BF) e semitendinosus (ST) durante a execução do agachamento afundo até à exaustão com o membro inferior posicionado frontalmente e posteriormente. Participaram do estudo nove … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In badminton, lunge is frequently employed as a fundamental step, and when players grow tired, they are more likely to suffer ankle injuries in addition to knee injuries during practice or competition ( Herbaut et al, 2018 ). Garcia et al (2012 ), however, showed the lunge squat is an exercise that accurately represents the tiredness process and enhances knee stability by equally activating the quadriceps and hamstring complexes, and this co-activation Weir et al (1998 ) observed to occur simultaneously with fatigue. The fatigue process reduces the contraction force and muscle activation time of the quadriceps, which triggers an increase in hamstring muscle activity during fatigue ( Garcia et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In badminton, lunge is frequently employed as a fundamental step, and when players grow tired, they are more likely to suffer ankle injuries in addition to knee injuries during practice or competition ( Herbaut et al, 2018 ). Garcia et al (2012 ), however, showed the lunge squat is an exercise that accurately represents the tiredness process and enhances knee stability by equally activating the quadriceps and hamstring complexes, and this co-activation Weir et al (1998 ) observed to occur simultaneously with fatigue. The fatigue process reduces the contraction force and muscle activation time of the quadriceps, which triggers an increase in hamstring muscle activity during fatigue ( Garcia et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“… Garcia et al (2012 ), however, showed the lunge squat is an exercise that accurately represents the tiredness process and enhances knee stability by equally activating the quadriceps and hamstring complexes, and this co-activation Weir et al (1998 ) observed to occur simultaneously with fatigue. The fatigue process reduces the contraction force and muscle activation time of the quadriceps, which triggers an increase in hamstring muscle activity during fatigue ( Garcia et al, 2012 ). By preventing external joint rotation, the quadriceps, hamstrings, and gastrocnemius muscles stabilize the knee ( Winby et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%